Improvement of electron injection of organic light-emitting devices by inserting a thin aluminum layer into cesium carbonate injection layer - 辛利文 吴晓明 华玉林 肖志慧 王丽 张欣 印寿根 (Chinese physics B, 2015)
We investigate the electron injection effect of inserting a thin aluminum（Al） layer into cesium carbonate（Cs2CO3）injection layer. Two groups of organic light-emitting devices（OLEDs） are fabricated. For the first group of devices based on Alq3, we insert a thin Al layer of different thickness into Cs2CO3 injection layer, and the device＇s maximum current efficiency of 6.5 cd/A is obtained when the thickness of the thin Al layer is 0.4 nm. However, when the thickness of Al layer is 0.8 nm, the capacity of electron injection is the strongest. To validate the universality of this approach, then we fabricate another group of devices based on another blue emitting material. The maximum current efficiency of the device without and with a thin Al layer is 4.51 cd/A and 4.84 cd/A, respectively. Inserting a thin Al layer of an appropriate thickness into Cs2CO3 layer can result in the reduction of electron injection barrier, enhancement of the electron injection, and improvement of the performance of OLEDs. This can be attributed to the mechanism that thermally evaporated Cs2CO3 decomposes into cesium oxides, the thin Al layer reacts with cesium oxides to form Al–O–Cs complex, and the amount of the Al–O–Cs complex can be controlled by adjusting the thickness of the thin Al layer.